An Enterprise Architecture Plan For Balai Riset dan Standardisasi Industri Bandar Lampung - Anton Catur Atmoko; Sutedi Sutedi (Prosiding International conference on Information Technology and Business (ICITB), 2021)
Baristand Industri Bandar Lampung is a government agency that has a vision and mission to become a professional and competitive testing, inspectionand calibration service agency. In order to realize its vision and carry out its mission, Baristand Industri Bandar Lampung requires the support of adequate facilities to carry out itsbusiness processes as a Testing Institute, Technical Inspection Institute and Calibration Institute. In carrying out its business processes, the Baristand Industri Bandar Lampung does not yet have an automated and integrated system. So far,the services provided have been carried out using computer aids, but have not used special centralized applications. This study aims to design Enterprise Architecture (EA) using the Federal Enterprise Architecture Framework (FEAF) with the aim of producing a blueprint containing business, information and technology architecture modeling that is used as a reference for creating and developing informationtechnology in accordance with the business objectives of the Baristand Industry Bandar Lampung. The results of this study are to design information systems at the Baristand Industri Bandar Lampung, in the form of semantic models, activity diagrams, Entity Relationship Diagrams (ERD), sitemap, network architecture, table structures in databases, information system input and output, hardware and software requirements for operating systems, Data Definition Language (DDL), methods and addressing for internet connection.Keywords—Baristand Industry Bandar Lampung, Enterprise Architecture, FEAF